A Picture Book Based on Sasambo Local Wisdom to Enhance Elementary School Students’ Cultural Literacy - Melinda Septiani; Sukri; Syaiful Musaddat; Sukardi; Asrin (Universitas Pendidikan Ganesha, 2026)
Students’ cultural literacy is still relatively low due to the lack of reading materials based on local wisdom. This study aims to produce a product in the form of a picture book based on Sasambo local wisdom to improve the cultural literacy of elementary school students. The research method used is RnD (Research and Development) with the ADDIE model which contains 5 stages, namely analysis, design, development, implementation, and evaluation. Data collection techniques used were interviews, observations, questionnaires, and tests. The data analysis employed validity, practicality, and effectiveness tests. The results of the study showed that at the analysis stage, elementary school students’ cultural literacy was still low due to the limited reading materials based on local culture. The results of statistical testing using the paired sample t-test obtained a significance of <0.001 (smaller than 0.05) which means there is a significant difference between the pretest and posttest scores. Based on the study findings, it will be concluded that the picture book based on Sasambo local wisdom is effective in improving the cultural literacy of elementary school students. The research implications indicate that locally based picture books can be utilized as contextual learning resources and support the strengthening of students' cultural identity in elementary schools.